Unraveling structural poverty: Insights from small-scale fishermen’s households on the coast of Muara Gembong, Indonesia - Taufik, Iswan; Kinseng, Rilus A.; Pandjaitan, Nurmala K. (Center for Sociological Studies and Community Developmen, 2025)
Structural poverty in Muara Gembong District, Bekasi Regency, Indonesia, remains a serious issue affecting small-scale fishermen. This study examines the poverty conditions of fishermen’s households using quantitative and qualitative approaches. A census of 31 households and interviews with 5 key informants reveal that all households’ experience income decline during the lean season, keeping them below the poverty line. The stark income fluctuations between fishing and non-fishing periods show their economic vulnerability. Poverty among these fishermen is multidimensional, covering inadequate access to food, health, housing, and education-meeting the definition of poverty in Law No. 13 of 2011 Republic of Indonesia on Handling the Poor. Using Anthony Giddens’ structuration theory, poverty is interpreted as the result of interactions between social structures and individual agency. The study uniquely applies this theory to explore fishermen’s poverty from a multidimensional perspective. Findings show that political-economic structures, environmental degradation, policy failures, limited capital and technology, patron-client systems, and unequal market access restrict social mobility. To overcome these challenges, comprehensive and cross-sectoral policy interventions are required to address the structural roots of poverty and improve the resilience and welfare of small-scale fishermen.